Implicit Methods for Equilibrium Problems on Hadamard Manifolds - Muhammad Aslam Noor; Saira Zainab; Yonghong Yao (Journal of Applied Mathematics)
We use the auxiliary principle technique to suggest and analyze an implicit method for solving the equilibrium problems on Hadamard manifolds. The convergence of this new implicit method requires only the speudomonotonicity, which is a weaker condition than monotonicity. Some special cases are also considered.